Study and Analysis on Stress Safety Judgment Method of Heavy Vehicle Rolling on Long-Distance Pipeline. (1st July 2022) - Shi, Ning; Jiang, Jinxu; Geng, Lin; Zhang, Liwen; Niu, Yakun; Wang, Kaimeng
Abstract : With the rapid increasing mileage of China's long-distance oil and gas pipelines, the intersection construction with other civil engineering, encroachment by invading the pipeline route, and other third-part problems occurred occasionally. Heavy vehicles rolling the serving pipeline have become one of the inevitable safety risks. The field test method of three in-service long oil and gas pipelines under heavy vehicle rolling is elaborated. The pipeline stress and soil pressure during tests are monitored and analyzed. The parametric model of pipe mechanical response under heavy vehicle rolling and stacking load is established, and the quantitative feedback of each parameter on pipeline stress safety response under heavy vehicle rolling is formed. The results show that the influence factors such as vehicle weight, vehicle speed, buried depth of pipeline, horizontal distance and cover plate on the stress state, vertical displacement state, and contact stress of pipe soil interface are highly consistent with the finite element method and test method, which could be a guideline for the safety assessment at rolling site.